Penentuan Quru' Masa Iddah Perceraian - Via Asmaus Sa'adah (At-Ta'aruf : Jurnal Hukum Keluarga Islam, 2023)
Divorce imposed by the husband has consequent rights and obligations that must be fulfilled by each party, one of which is the obligation to observe iddah. This research discusses the post-divorce quru'iddah calculations that must be carried out, especially by the ex-wife. This research is library research with qualitative descriptive methods. The approach used is normative juridical. The data collection technique uses literature in the form of books, notes, and the results of research reports from previous research. The results of this research show that there are differences in determining the quru'iddah for divorce from the perspective of the Syafi'i school and the KHI, including the fact that there is no mention of how long the mandatory iddah is for women with Istiḥāḍāḥ in the KHI, which of course can cause legal chaos due to their ignorance in calculating menstrual law and Istiḥāḍāḥ. While in the Syafi'i school of thought the detailed description is very clear, then for women with Amenorrhoea status there is also a very significant difference, namely that the woman has to wait until the time of menopause arrives in the perspective of the Syafi'i school of thought which will certainly be burdensome for both parties, both the wife undergoing iddah. and husbands who continue to provide iddah maintenance after divorce, but only provide it for up to one year according to the KHI perspective, but this has caused a lot of controversy, especially among fanatics of the Shafi'i school of thought. Keyword: Quru’, Mazhab Syafi’i, KHI.